Palm Oil in Southeast Asia: A Regional Bibliometric Analysis of Research Production, Collaboration, and Influence - Judijanto, Loso (Westscience Press, 2025)
This study offers a regional bibli⁠ometric analysis of palm oil research in Southeast As⁠ia f⁠rom 2000 to 2025,⁠ int⁠egrating per⁠formance metrics with networks of co-authorship, co-occurrence, co-citation, and bibli⁠ographic cou⁠pling. The f⁠indings indicate a concentrated commodity-region nexus centered on⁠